(untitled) (Comprehensive Journal of Science, 2025)
use systems in shops is crucial for enhancing efficiency These systems manage sales transactions and include features such as inventory tracking, customer management, and sales reporting. These systems usually used Databases that organized collections data by these systems in shops but with long working these systems for long years the size for these database become bigger than when start work that makes the systems in shops work slowly and least efficiency their size refers to the amount of data stored within them, typically measured in bytes, kilobytes (KB), megabytes (MB), gigabytes (GB), terabytes (TB), or even larger units like petabytes (PB) for large-scale systems. There are many Types of Databases such as MySQL, PostgreSQL, Oracle, Microsoft SQL Server. Size of database : Usually well-suited for small to medium-sized datasets but can scale to terabytes and beyond with proper indexing, partitioning, and optimization. With the continuous use of these systems in commercial stores and the increase in operations on them, such as updating and deleting data and adding data to the database, their efficiency decreases and their slowness increases. This phenomenon is called database inflation or database bloat.